HUBUNGAN MATA KULIAH PENDIDIKAN KEWARGANEGARAAN DENGAN PENINGKATAN WAWASAN KEBANGSAAN DAN SEMANGAT NASIONALISME MAHASISWA - Sofyan, Fitri Silvia; Sundawa, Dadang (Universitas Pendidikan Indonesia, 2015)
This research is purposed to procure representation about correlations between civic education courses with the students’ insight into nationalism and the students’ spirit of nationalism in STKIP Garut. This study used quantitative approach with a correlation study method. The data of this study was obtained through questionnaires and tests given to students in STKIP Garut. Researcher revealed that: 1. The implementation of civic education as a general basic course included in personality development course in STKIP Garut had been implemented very well and was able to make a significant contribution, which is in accordance to civic education’s goal itself. 2. Students in STKIP Garut were believed to have a good insight into nationalism and a strong nationalism. 3. The application of civic education courses as a general basic course has a strong correlation and a great influence on the improvement of the students’ insight into nationalism and the spirit of nationalism in STKIP Garut.Keywords: Civic education course, nationality, insight on nationalism, spirit of nationalism, STKIP Garut.